1868-69 N.C. Sess. Laws 407-08 - (:unkn) unknown (My University, 1868)
Pub. Laws, ch. 167, § 7: Every person who commits any assault upon the person of another, with any deadly or dangerous weapon, or who unlawfully shoots or attempts to shoot at another with any kind of fire-arms, with intent to injure any person, without intent to kill such person or to commit any felony, shall be punished upon conviction, by imprisonment in the State's prison not exceeding five years.
Keywords: COMMITTING CRIME W/ WEAPON